Diet and Nutrition Advice After a Solid Tumor Diagnosis. Issue 7 (July 2021) - Mullee, Amy; O'Donoghue, Aidan; Dhuibhir, Pauline Uí; O'Donoghue, Niamh; Burke, Deirdre; McSharry, Veronica; Stewart, Gillian; Casey, Louise; Donnelly, Yvonne; Gallagher, Julie; Higgins, Kiera; Roulston, Fiona; et al.
Abstract : PURPOSE: Credible evidence-based diet and nutrition advice is essential for patients with cancer. This study aimed to explore what advice patients with cancer obtained before a formal dietetic visit. METHODS: A multicenter, observational study was conducted in seven hospital-based oncology services. Consecutive patients were recruited at first dietetic assessment. In addition to routine dietetic assessment, participants completed a four-item questionnaire describing diet and nutrition advice obtained since diagnosis. RESULTS: Seventy-seven patients participated. More than 80% had multiple nutrition-impact symptoms. In total, 53 (69%) obtained advice from professional and nonprofessional sources before dietetic visit. Family and friends were the most common sources of advice. More than one third got advice from (nondietetic) healthcare professionals. Most advice related to "foods to include" (61%) and "foods to avoid" (54%) in the diet. Many of the "foods to avoid" were important sources of micro- and macronutrients. Advice about dietary supplements (31%) and specific diets (28%) was common, rarely evidence-based, and frequently contradictory. Participants found it difficult to discern what advice was trustworthy and reliable. Despite this, most followed the advice. CONCLUSION: The majority of patients received diet and nutrition advice before first dietetic visit. Most of this came from nonprofessional sources. Any advice from nondietetic healthcare professionals was inconsistent or vague. This was mainly related to the avoidance and/or inclusion of particular foods and was often contradictory. Nevertheless, patients usually followed such advice fully. To help manage their frequent nutrition-impact symptoms and resolve the contradictory advice they had received, many expressed the need for earlier professional dietetic consultation.